Handgrip Strength Predicts Difficult Weaning But Not Extubation Failure in Mechanically Ventilated Subjects - Cottereau, Guillaume; Dres, Martin; Avenel, Alexandre; Fichet, Jérome; Jacobs, Frédéric M; Prat, Dominique; Hamzaoui, Olfa; Richard, Christian; Antonello, Marc; Sztrymf, Benjamin (Respiratory care, 2015)
Muscle weakness, defined by the Medical Research Council scale, has been associated with delay in mechanical ventilation weaning. In this study, we evaluated handgrip strength as a prediction tool in weaning outcome. This was a 1-y prospective study in 2 ICUs in 2 university hospitals. Adult patients who were on mechanical ventilation for at least 48 h and eligible for mechanical ventilation weaning were screened for inclusion. Handgrip strength was evaluated using a handheld dynamometer before each spontaneous breathing trial (SBT). Attending physicians were unaware of handgrip strength and decided on extubation according to guidelines. Eighty-four subjects were included (median age 66 [53-79] y, with a median Simplified Acute Physiology Score II of 49 [37-63]). At the first evaluation, median handgrip strength was significantly associated with weaning outcome as defined by international guidelines: simple (20 [12-26] kg), difficult (12 [6-21] kg), or prolonged (6 [3-11] kg) weaning (P = .008). Time to liberation from mechanical ventilation and ICU stay were significantly longer for subjects classified as having muscle weakness according to the handgrip strength-derived definition (P = .02 and P = .03, respectively). In multivariate analysis, known history of COPD (odds ratio [OR] 5.48, 95% CI 1.44-20.86, P = .01), sex (OR 6.16, 95% CI 1.64-23.16, P = .007), and handgrip strength at the first SBT (OR 0.89, 95% CI 0.85-0.97, P = .004) were significantly associated with difficult or prolonged weaning. Extubation failure, as defined by re-intubation or unscheduled noninvasive ventilation within 48 h after extubation, occurred 14 times after 92 attempts, leading to an extubation failure rate of 15%. No association was found between handgrip strength and extubation outcome. Muscle weakness, assessed by handgrip strength, is associated with difficult or prolonged mechanical ventilation weaning and ICU stay, but not with extubation outcome.